SOCIAL-HYGIENIC ASPECTS OF PREVENTION OF HARMFUL EATING HABITS AMONG YOUNG PEOPLE - Старішко, О.М.; Єрошкіна, Т.В. (World of Medicine and Biology, 2016)
Unhealthy lifestyle of adult population suggests, that many Ukrainians don’t realize the risks they are exposed too. That is unhealthy lifestyle – smoking, alcohol abuse, poor nutrition and lack of exercise – is one of the main causes of high morbidity. This causes the relevance of this study. Among the main reasons for the emergence and spread of harmful habits we can be call like: social coherence. If one or the other model of behavior adopted in the group, which a person belongs to,or which he identificeret yourself with, he feels the need to follow it to show their affiliation to this group, and thence fashion a bad habit; Satisfaction. One of the main reasons why people succumb to bad habits – is a related and enjoyable (firstly) feelings, from wellness and relaxing to the mystical euphoria. This issue can be showed also through the prism of psychological knowledge. The motives of the first tobacco and alcohol consumption, most interviewed children in the first place put forward the motive of “it was interesting”. Therefore, we can conclude that a significant impact on attracting young people to psychotropic substances use has a negative environment. Smoking, excessive alcohol use, other substance use not only increases the risk of cardiovascular disease, but also is the reason for the growing mortality due to accidents and injuries. An important component of prevention with addictions is the formation of teenagers' positive motivation to assimilate health knowledge and care about their health, the formation of a belief system in the minds of students, which is based on the effective use of healthy potential of people's habits and rituals.
Keywords: harmful eating; youth; prophylaxis